Corneal biomechanics after rigid gas permeable contact lens wear in keratoconus eyes - ShokrollahzadehFereshteh; HashemiHassan; JafarzadehpurEbrahim; MirzajaniAli; KhabazkhoobMehdi; AsgariSoheila (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
Background: Evaluation of corneal biomechanical properties 3 months after using rigid gas permeable (RGP) contact lenses in keratoconus. Methods: In this prospective trial study, cases were 32 keratoconic eyes with no history of RGP lens wear. All eyes were examined with the Ocular Response Analyzer (ORA) and the Corneal Visualization Scheimpflug Technology (CORVIS-ST) to measure corneal hysteresis (CH), corneal resistance factor (CRF), deformation amplitude (DA), applanation velocity (AV) 1 and 2, applanation length (AL) 1 and 2, and peak distance before and 3 months after fitting aspheric RGP lenses. The effect of the correlation between contralateral eyes and maximum keratometry were controlled for in the analysis. Results were compared using repeated measures analysis of covariance. Results: At 3 months, neither the increases in mean CH (0.14±2.77 mmHg, P=0.789), CRF (0.41±4.35 mmHg, P=0.612), AV1 (0.03±0.17 m/s, P=0.301), AV2 (0.11±0.59 m/s, P=0.299), AL1 (0.44±1.56 m/s, P=0.118), AL2 (1.16±5.06 m/s, P=0.211), and peak distance (0.19±1.29 m/s, P=0.409), nor the decrease in mean DA (0.03±0.17 mm, P=0.402) was statistically significant. Conclusions: Results in our series of patients indicated that 3 months of RGP lens wear had no significant impact on corneal biomechanics, and perhaps non progression of keratoconus. Therefore, RGP lenses can be regarded safe and appropriate in keratoconic patients.